The Darker Side of Near-Death Experiences - Greyson, Bruce (Journal of Scientific Exploration, 2023)
Modern research on near-death experiences (NDEs), powerful spiritual experiences triggered by a close brush with death, has focused on experiences characterized by profound positive feelings, ranging from incredible peace and calmness to bliss and ecstasy. However, throughout history there have been accounts of frightening deathbed visions and terrifying journeys to a hellish realm peopled by evil forces or beings. It is difficult to determine the prevalence of these distressing NDEs because the anxiety and judgmentalism they evoke deter experiencers from acknowledging and revealing them. Nevertheless, most recent studies estimate their prevalence at between 11% and 22% of all NDEs. Their phenomenology varies widely, but attempts to categorize distressing NDEs have yielded several distinct types. Various researchers have attributed distressing NDEs to the personal characteristics of the experiencer, to biological factors of the brush with death, or to other circumstances around the event. Overall, distressing NDEs appear to be associated with fewer permanent aftereffects than the more common pleasant NDEs, which may reflect the reluctance of experiencers to focus attention on unpleasant experiences. Nevertheless, some distressing NDEs lead to long-lasting emotional trauma. Several strategies have been described by which experiencers try to come to terms with and find meaning in, their distressing NDEs. Much research remains to be done on the causes and aftereffects of distressing NDEs and their relationship to other dark spiritual experiences.